What's in the R- Stars for Korea? - Rafiq, Sohrab (IMF Working Papers; Working Paper, 2021)
Korea's stars tell of an economy saddled with a real neutral rate (r-star) that has declined significantly in recent decades and is currently below zero. This reflects a significant decline in trend growth, and two large financial crises that triggered significant shifts in the saving-investment balance. Larger fiscal deficits and frothy financial conditions since 2012 have helped offset rising demand for safer assets, preventing the neutral rate from falling further. Nonetheless, the fall in the neutral rate, coupled with its effects on asset returns, has complicated the task of monetary policy stabilization. Korea's neutral rate is likely to remain low over the medium-term and could fall further, reflecting a structural savings-investment imbalance owing to declining productivity and a rotation in demographics increasing the demand for precautionary saving and convenience yield, and widening the capital risk premia. The COVID pandemic risks magnifying these trends.